2018
DOI: 10.1111/anu.12854
|View full text |Cite
|
Sign up to set email alerts
|

Citrus x aurantiumessential oil as feed additive improved growth performance, survival, metabolic, and oxidative parameters of silver catfish (Rhamdia quelen)

Abstract: The effects of dietary supplementation of graded level (0, 0.25, 0.5, 1.0, and 2.0 ml/kg diet) of Citrus aurantium essential oil (EOCA) on the growth, metabolic, and oxidative parameters of silver catfish (Rhamdia quelen) were investigated in a 60‐day growth trial. Fish fed with 2.0 ml EOCA per kg exhibited significantly better growth performance than those fed the control diet. Glucose, lactate, and protein levels in liver and muscle were altered significantly by dietary addition of EOCA. Hepatic lipid peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
4
15
2
Order By: Relevance
“…In this study, tambaqui fed 0.25 and 2.0 ml EOCL/kg diet showed a reduction in the muscle lactate level compared to the control fish. In line with the present study, Lopes et al (2019) reported a reduction in muscle lactate levels in silver catfish fed a diet supplemented with the EO of C. aurantium . These authors reported that the lactate might have been mobilized to maintain normoglycaemia by gluconeogenesis in the silver catfish.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, tambaqui fed 0.25 and 2.0 ml EOCL/kg diet showed a reduction in the muscle lactate level compared to the control fish. In line with the present study, Lopes et al (2019) reported a reduction in muscle lactate levels in silver catfish fed a diet supplemented with the EO of C. aurantium . These authors reported that the lactate might have been mobilized to maintain normoglycaemia by gluconeogenesis in the silver catfish.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the addition of 0.5 and 1.0 ml EOCL/kg diet resulted in a significant reduction in muscle glycogen reserves, and those fed 2.0 ml EOCL/kg diet presented lower hepatic and muscular glucose levels compared to the control group, suggesting that the tambaqui might have used these reserves to maintain normoglycaemia. These data are in concurrence with the recent findings of Lopes et al (2019), who also determined a decrease in muscle glycogen reserves in silver catfish fed 1.0 ml of bitter orange oil ( Citrus × aurantium ). Baba et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…peels are rich in numerous biologically active compounds, such as vitamin C, phenolic acids, pectin and flavonoids (Bocco, Cuvelier, Richard, & Berset, ; Manthey & Grohmann, ; Rafiq et al, ) having potential anti‐allergenic, anti‐atherogenic, anti‐inflammatory, antimicrobial, antioxidant, antithrombotic, cardioprotective and vasodilatory effects (Benavente‐García, Castillo, Marin, Ortuño, & Del Rio, ; Middleton, Kandaswami, & Theoharides, ). Several studies on dietary inclusion effects of citrus meal and citrus by‐products fermented on olive flounder ( Paralichthys olivaceus , Temminck & Schlegel) (Lee et al, ; Seo, Kim, Son, & Lee, ) and red sea bream ( Pagrus major Temminck & Schlegel) (Song, Park, Lee, & Lee, ), citrus ( Citrus unshiu Marcovitch) pomace on abalone ( Haliotis discus discus , Reeve) (Jwa & Yeo, ), C. aurantium Linnaeus oil on silver catfish ( Rhamdia quelen Quoy and Gaimard) (Lopes et al, ) and essential oils extracted from bitter lemon ( C. limon Osbeck) peels on fish ( Labeo victorianus Boulenger) (Ngugi, Oyoo‐Okoth, & Muchiri, ) have been reported. Therefore, CPB seems to have high potential as an alternative source for MA in abalone feed as well.…”
Section: Introductionmentioning
confidence: 99%